Integration of social responsability in the curricula: a case study (Journal of Business, Universidad del Pacífico (Lima, Peru), 2015)
The document presented below combines the review of existing literature in the field of teaching ethics and social responsibility with a case study through which the integration of social responsibility is analyzed transversely in the curricula of undergraduate programs offered by a Peruvian university specializing in economics and business. An analysis method that exploits the concept of social responsibility defined in ISO 26000, to generate items that allow to evaluate the approach to social responsibility for the contents of 215 compulsory courses offered by the different academic departments of the university was created. The review of the courses was conducted using the discernment of five experts. The first contribution of this research is to design a transferable and replicable method for mapping if a generic competence, as is the social responsibility develops gradually throughout the whole training process. On the other hand, the case study shows that 21% of the courses offered address some of the subjects of social responsibility
Keywords: Social responsibility; Case study; Corporate social responsibility education; ethics education; teaching corporate social responsibility